A Mondrian matrix of seasonal patterns of Culicoides nulliparous and parous females at different latitudes in Spain. (April 2020) - Barceló, Carlos; Estrada, Rosa; Lucientes, Javier; Miranda, Miguel A.
Abstract: Insects from genus Culicoides (Diptera; Ceratopogonidae) transmit arboviruses such as Bluetongue virus (BTV); affecting wild and domestic ruminants. These insects are age graded for monitoring purposes in surveillance programs. Parous females (PF) are the only fraction of the entire population that could effectively transmit viruses in a subsequent blood meal. Data of the Spanish Entomosurveillance National Program from 2008 to 2010 were used to analyse the seasonal pattern of the nulliparous females (NF) and PF of the vector species Obsoletus complex, C. imicola, C. newsteadi and C. pulicaris . Latitude variation on the seasonal abundance patterns of PF was also analysed in trap sites spanning a North-South axis in mainland Spain. The weekly abundance of PF was always highest in summer. The peak of abundance mainly occurred between April and July except for C. imicola that was from September to November. The analysis of the latitudinal seasonal variation of PF in Spain showed that Northern provinces have absence of C. imicola while the Obsoletus species were more present in Northern areas. There were periods of the year were no individuals of any vector species were collected, which should be considered in order to calculate the Seasonally Vector-Free Period (SVFP). Culicoides newsteadi and C. pulicaris exhibited the highest population in Toledo, probably related to their inland preferences. These findings would be of interest for a better understanding of the periods of low and high risk of transmission of BTV in Spain. Highlights: The weekly abundance of Culicoies parous females was always highest in summer. Periods with absence of Culicoides vector species should be considered to calculate the Seasonally Vector-Free Period. Northern provinces have absence of C. imicola while the Obsoletus species were more present in Northern areas. Culicoides newsteadi and C. pulicaris exhibited preferences for inland locations.